College-Age Millennials' Preferences for Food Supplied by Urban Agriculture - Printezis, Iryna; Grebitus, Carola (Frontiers in Sustainable Food Systems, 2020)
Millennials are the largest generation, yet. As a result, their preferences are critical when it comes to evaluating success of urban agriculture. Using two online choice experiments, this paper investigates the preferences and willingness to pay of college student millennials for unprocessed (fresh) or processed (typically come in a container) food products sold at urban farms. We also examine whether competing points of sale and other attributes, such as organic, affect preferences and willingness to pay for urban farm food. We find that, on average, college-age millennials are willing to pay a premium for local food. However, they are not willing to pay premiums for local food that is sold at farmers markets, and discount it when it is purchased directly from an urban farm. Our findings suggest that, if the goal is to increase the sales of urban farm food, targeted promotions are needed. Urban farms have to show the value from purchasing products through their channels to college-age millennials or seek the means to supply their food through grocery stores.